Iron Supplement Adherence, Dietary Intake, and Anemia Risk among Adolescent Girls in Madiun Regency, Indonesia - Taufiqurrahman, Taufiqurrahman; Hafid, Fahmi; Mujayanto, Mujayanto; Nuswantari, Atika; Ratno, Ratno; Rahayuningtyas, Rina; Prasetyawan, A. E.; Sri Rahayu, Yayuk (Journal of Health and Nutrition Research, 2025)
Anemia among adolescent girls remains a significant public health concern, impairing growth, learning, productivity, and reproductive health. This cross-sectional study examined the relationship between iron supplement adherence, dietary intake, nutritional status, and anemia among 105 female students aged 12–15 years in Madiun Regency, Indonesia, using a total sampling approach. Data collection included anthropometric measurements, dietary intake assessed with a semi-quantitative food frequency questionnaire (SQ-FFQ), hemoglobin levels measured by point-of-care testing, and iron supplement adherence, with anemia defined as hemoglobin <12 g/dL. The prevalence of anemia was 14.3%. While 88.6% of respondents adhered to iron supplements, non-adherence was associated with a 24.5-fold higher risk of anemia (p < 0.001). Most participants reported inadequate dietary intake, specifically in terms of energy (79.0%), protein (76.2%), zinc (62.9%), and iron (93.3%). Nutritional intake and BMI-based nutritional status showed no significant association with anemia, although non-chronic energy deficiency (non-KEK) was linked to a higher prevalence (p = 0.030). In conclusion, adherence to iron supplementation strongly protects against anemia; however, poor dietary quality remains a challenge. Therefore, strengthening supervised supplementation programs, improving school-based dietary quality, and implementing regular hemoglobin screening are recommended to reduce the risk of anemia among adolescent girls.